Sports in literature : experiencing the thrill of competition through stories, poems, and nonfiction - Emra , Bruce (Lincolnwood, IL : National Textbook Co., 2000)
A collection of short stories, poems, essays, and non-fiction articles about various types of sports.
Includes index.
Keywords: Sports -- Literary collections; Sports -- Literary collections